Intradermal DNA vaccine delivery using vacuum-controlled, needle-free electroporation - Alison Generotti; Ryne Contreras; Brenden Zounes; Eric Schade; Andrea Kemme; Yatish Rane; Xinggang Liu; Dustin Elwood; Katherine Schultheis; Jeremy Marston; Jay McCoy; Kate Broderick; et al. (Elsevier, 2023)
Intradermal delivery of DNA vaccines via electroporation (ID-EP) has shown clinical promise, but the use of needle electrodes is typically required to achieve consistent results. Here, delivery of a DNA vaccine targeting the Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is achieved using noninvasive intradermal vacuum-EP (ID-VEP), which functions by pulling a small volume of skin tissue into a vacuum chamber containing noninvasive electrodes to perform EP at the injection site. Gene expression and immunogenicity correlated with EP parameters and vacuum chamber geometry in guinea pigs. ID-VEP generated potent humoral and cellular immune responses across multiple studies, while vacuum (without EP) greatly enhanced localized transfection but did not improve immunogenicity. Because EP was performed noninvasively, the only treatment site reaction observed was transient redness, and ID-VEP immune responses were comparable to a clinical needle-based ID-EP device. The ID-VEP delivery procedure is straightforward and highly repeatable, without any dependence on operator technique. This work demonstrates a novel, reliable, and needle-free delivery method for DNA vaccines.